The association between hemoglobin-to-red blood cell distribution width ratio and 28-day mortality in epidural hemorrhage: a cohort study - Hua Liu; Hua Liu; Hong Huang; Hong Huang; Jinrong Wang; Jinrong Wang; Wenming Wang; Min Ruan; Jiangang Liu (Frontiers in Neurology)
BackgroundThis study leverages the eICU collaborative research database (eICU-CRD) to investigate the relationship between the hemoglobin-to-red blood cell distribution width ratio (HRR) and 28-day mortality in patients with epidural hematoma (EDH).MethodsA total of 2,161 patients admitted between 2014 and 2015 with EDH were selected. Data included demographics, medical history, and laboratory tests. HRR was calculated and stratified into quartiles. Covariates included Glasgow Coma Scale (GCS), HDL, TG, hospital time, ICU time, LDL, age, BMI, gender, coma status, race, and medical conditions like COPD, CHF, and diabetes. Non-normal data distributions were analyzed using Kruskal-Wallis and chi-square tests, with logistic regression to explore the association of HRR and 28-day mortality.ResultsHigher HRR quartiles correlated with lower 28-day mortality (p = 0.024) and higher healthy discharge rates (p = 0.013). Univariate logistic analysis showed age positively associated with mortality (OR = 1.011, 95% CI: 1.004–1.018), while GCS, ICU time, hospital time, and HRR were negatively associated. Adjusted models confirmed an inverse relationship between HRR and mortality, with the fourth quartile showing a 40% reduced probability of mortality. Linear regression models indicated a 72% reduction in mortality risk per unit HRR increase and a critical HRR value of 1.12 for significant risk reduction.ConclusionHRR is significantly associated with 28-day mortality in EDH patients, with higher HRR values correlating with improved survival. ICU time also showed a correlation with reduced mortality, particularly up to a critical point.